Uma pedra no Rio Cuiabá : movimentos consolidantes do PPGE da UFMT (1988-2013) - Siqueira, Elizandra de (2014)
This research falls within the field of Education and studies of historical character, addressing the description and analysis of Post-Graduate Program in Education at UFMT. Its focus is through theoretical and empirical studies on the subject concerning the functioning of the program. The problem of this study structures itself on the understanding of how a program of postgraduate education sought to consolidate itself in approximately 25 years of existence, time coexisted setbacks and victories. These mishaps and victories confined in a specific dynamic operation, which thus allows building the research problem: what are the specifics of a program of postgraduate education in the Midwest of Brazil? The overall objective is to identify, describe and explain how its consolidation process in 25 years of its existence occurred in order to categorize knowledge about them. Specific objectives, seeks to: a) identify the essential configuration PPGE; b) describe the mentality of PPGE and key ideas present in PPGE; c) understand and explain the historical significance of PPGE between 1988 and 2013. hypothetical-deductive character, was based on methodologically micro-historical perspective Hartog (2006), Vainfas (2002), Revel (1998) and Sjizártó (2002). The thesis is presented: the Graduate Program in Education of the Federal University of Mato Grosso is an established institution of learning stricto sensu that reached a satisfactory level of quality through struggles and efforts of their own subjects from a historical perspective with settings, mentalities and pluralized and multifaceted key ideas in a process of discontinuation. Theoretical studies of Bourdieu (1996, 1998, 2004, 2009, 2010, 2011, and 2013) and the collected data support the thesis. The micro-story is constituted as a theory with methodological capacity to demarcate boundaries within an overall historical context, as the research has shown that the movements of the laws and decisions of higher bodies relating to postgraduate reach a greater or greatest profusion program as well as the program also fits into the process of building the graduate, linked to its insertion and social impact, because everything relates to everything. There is a considerable amount of people titrated by the program active in many areas of education, not only in Cuiaba or the State of Mato Grosso, as well as in other Brazilian and international universities. The PPGE/UFMT has considerable social inclusion when it is found that several of his masters and doctors involved in basic education and public administration linked to education. Externally, the PPGE/UFMT consolidates itself from the constant reconfiguration of its features, which emerge from the law on the graduate and CAPES evaluations.